The Influence of Experimental Methods on NaturalScience Learning Outcomes - Wildan (Education Studies and Teaching Journal (EDUTECH), 2024)
The purpose of this study was to determine the effect of the experimental methodon the learning outcomes of Natural Science in Class V students at MI Ash-ShobirinSamarinda and to find out how much influence the application of the experimentalmethod had on learning outcomes in Science in Class V students at MI Ash-ShobirinSamarinda. This study uses a quantitative approach with a quasi-experimentalresearch design. Data collection techniques using tests, observation anddocumentation. The test is used to determine student learning outcomes on theapplication of the experimental method. Observation is used to observe theteacher's ability to use the experimental method. And documentation is used fordata collection related to research. The variables in this study consisted of variableX experimental method and variable Y learning outcomes from science learning.The sample in this study were all fifth grade students at MI Ash-ShobirinSamarinda, totaling 45 people. The experimental class consisted of 23 students andthe control class consisted of 22 students. The data validity technique uses validityand reliability tests. The data analysis technique uses an independent T-test. Theresults obtained from the independent t-test in the experimental group against thecontrol group showed a significance value of 0.013 less than 0.05. Then it is statedthat Hₐis accepted and H₀ is rejected. It can be concluded that there is an effect ofthe use of the Experimental Method on the learning outcomes of natural scienceon single and mixed substances in class V students at MI Ash- Shobirin Samarinda.